Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
Home  >>  CBSE XII  >>  Math  >>  Differential Equations
0 votes

Find the general solution $e^x\tan y\;dx+(1-e^x)\sec ^2y\;dy=0$

Can you answer this question?

1 Answer

0 votes
  • Method of substitution can be followed if the function inthe numerator is a derivative of the function of the denominator.
Step 1:
Given $e^x\tan xdx + (1 - e^x)\sec^2ydy = 0$
On rearranging we get,
$(1-e^x)\sec^2ydy = - e^x \tan y dx$
$\large\frac{\sec^2ydy}{\tan y} = \frac{- e^xdx}{1-e^x}$
Step 2:
Using the information in the tool box, we understand that differentiation of $\tan y$ is $\sec^2y$ on the LHS and differentiation of $1-e^x$ is $-e^x$ on the RHS.
Hence now taking tany as t, then $dt = \sec^2y$ and take $u$ as $(1 - e^x)$, then $du = -e^x$
Hence the function can be written as $\large\frac{dt}{t} = \frac{du}{u}$
Step 3:
Now integrating on both sides we get,
$\log t = \log u + \log C $
$\log \tan y = \log(1-e^x)C$
$\tan y = C(1-e^x)$
This is the required solution.
answered Aug 14, 2013 by sreemathi.v
Ask Question
student study plans
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App